20th Century δ18O Seawater and Salinity Variations Reconstructed From Paired δ18O and Sr/Ca Measurements of a La Reunion Coral. Issue 12 (26th December 2019) - Pfeiffer, M.; Reuning, L.; Zinke, J.; Garbe‐Schönberg, D.; Leupold, M.; Dullo, Wolf‐Christian
Abstract: Sea surface salinity (SSS) is an important variable in the global ocean circulation. However, decadal to interdecadal changes in SSS are not well understood due to the lack of instrumental data. Here we reconstruct SSS from a paired, bimonthly resolved coral δ 18 O and Sr/Ca record from La Reunion Island that extends from 1913 to 1995. Coral Sr/Ca correlates with regional sea surface temperature (SST) back to 1966, when instrumental coverage is good, while coral δ 18 O does not. The slope of the monthly (annual mean) coral Sr/Ca‐SST regression is −0.040 mmol/mol per 1 °C (−0.068 mmol/mol per 1 °C) consistent with published estimates of the Sr/Ca‐SST relationship. Coral Sr/Ca suggest a warming of 0.39 °C since 1913. δ 18 O seawater is calculated by subtracting the temperature component from measured coral δ 18 O, using coral Sr/Ca as well as historical SST products. The derived δ 18 O seawater reconstructions are correlated ( r > 0.6), and all show a significant shift in the midtwentieth century (−0.17‰ to −0.19‰), indicating a freshening of SSS by 0.7 psu. However, the timing of this shift depends on the temperature component and varies from 1947 (δ 18 O seawater calculated with historical SST) to the late 1950s (δ 18 O seawater calculated with coral Sr/Ca). Coral Sr/Ca shows warm temperature anomalies in the mid‐1950s, while historical SST products show warm anomalies from 1940 to 1945 followed by cooling in the 1950s, a pattern typical for the World War II bias. This suggests that historical SST may bias reconstructions of δ 18 O seawater and SSS from corals. Key Points: La Reunion coral oxygen isotopes record changes in the isotopic composition of seawater/salinity, while Sr/Ca ratios record temperature The coral record suggests a significant freshening in the mid‐20th century Potential biases in historical temperature data may influence δ 18 O seawater/salinity reconstructions from corals